The Effect of Tuai Padi Culture and Religiosity on The Public Welfare in Kerinci Regency - Khusairi, Halil; Sarmigi, Elex (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This study aims to see whether the public welfare can be shaped by the culture and religiosity of the Public. Therefore, this research was conducted on the people of Kerinci Regency who consistently maintain their ancestral culture, namely the rice harvest feast culture, besides that the majority of the people of Kerinci Regency also adhere to Islam. So for the purposes of this study, a sample of 435 respondents was taken using purposive sampling technique. To analyze the data, multiple linear regression analysis was carried out with the help of the IBM SPSS 25 application. The results of this study found that both partially and simultaneously the culture of rice harvest and religiosity had an effect on the public welfare of Kerinci Regency, with a magnitude of 39.3%.